Experimental Study on Strength of Concrete with Partial Replacement of Fine Aggregate with Brick Waste - Htike, Pyae Su (วารสารวิชาการ มหาวิทยาลัยราชภัฏอุตรดิตถ์, 2020)
This paper aims to achieve the green concrete making process by using recycled materials to lessen the negative impact on the environment. In this paper, the wasted bricks from brick manufacturing factories are reused as fine aggregate in the concrete making process. The brick dust is mixed into 5%, 15%, and 25% by weight of fine aggregate. Then the results from concrete specimens with brick powder are compared with the results of conventional concrete. The compressive and splitting tensile strengths of concrete samples are verified at designated curing days of 7 days, 14 days, and 28 days. After all of the strength tests, the standard deviation is calculated to analyze the errors in the results of concrete specimens by comparing them to conventional concrete. In this research, the concrete specimen with 5% of brick powder is the optimum value at compressive strength with 31.6 N/mm2 and the concrete specimen with 25 % of brick powder is the optimum value at splitting tensile strength with 1.39 N/mm2. The optimum result at compressive strength is succeeded with concrete specimen with the lowest composition of brick powder and vice versa, concrete specimens with the highest composition of brick powder achieves the optimum result in splitting tensile strength in this research.